1986
DOI: 10.1007/bf01531709
|View full text |Cite
|
Sign up to set email alerts
|

Autism, mental retardation, and chromosomal abnormalities

Abstract: There are reports of sex chromosomal abnormalities including XXY, XYY, and fragile X karyotypes in autistic individuals, but structural autosomal defects have rarely been reported. This paper presents four patients with autism, mental retardation, minor dysmorphic features, and structural autosomal defects. These patients shared autistic features including fascination with inanimate objects, catastrophic reactions to changes in their environment or their daily routine, echolalia, and poor relatedness; IQ score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Considering the potential role of neuroligins in dictating the E/I ratio, aberrations in the expression of these proteins may be associated with these disorders. Consistent with this, rearrangement of chromosomal regions harboring neuroligin genes have been linked to autism [137][138][139][140][141][142][143]. Other investigations have revealed that mutations in neuroligin 3 and neuroligin 4 are associated with autism [78,[143][144][145].…”
Section: Diseases Associated With Neuroligin Family Member Dysfunctionmentioning
confidence: 91%
“…Considering the potential role of neuroligins in dictating the E/I ratio, aberrations in the expression of these proteins may be associated with these disorders. Consistent with this, rearrangement of chromosomal regions harboring neuroligin genes have been linked to autism [137][138][139][140][141][142][143]. Other investigations have revealed that mutations in neuroligin 3 and neuroligin 4 are associated with autism [78,[143][144][145].…”
Section: Diseases Associated With Neuroligin Family Member Dysfunctionmentioning
confidence: 91%
“…Autism was reported in at least four patients exhibiting the Smith-Magenis deletion (Cabral de Almeida, Reis, & Martins, 1989;Lockwood et al, 1988;Mariner et al, 1986;Vostanis, Harrington, Prendergast, & Farndon, 1994). To date, it is not possible to estimate the absolute or relative prevalence of the syndrome within autism.…”
Section: Smith-magenis Syndromementioning
confidence: 94%
“…All presently identified neuroligin-3 and -4 mutations result in a loss of function, either attributable to truncation or a point mutation of the cholinesterase domain, which result in intracellular retention (Chih et al, 2004;Comoletti et al, 2004). Furthermore, it appears that point mutations and chromosomal rearrangements in regions of the genome containing the genes for neuroligin-2 and PSD-95 are associated with autism (Mariner et al, 1986;Risch et al, 1999).…”
Section: Role For Neuroligin and ␤-Neurexin In Excitatory Synapse Formentioning
confidence: 99%